Corrigendum to “Increased detection rate of melamine-containing calcium urolithiasis by using matrix-assisted laser desorption/ionization time-of-flight mass spectrometry technique in clinical practice” [Clin. Chim. Acta 431C (2014) 294–298] - Wu, Chia-Fang; Liu, Chia-Chu; Chou, Yii-Her; Shiea, Jentaie; Shen, Jung-Tsung; Wang, Shiun-Shiuan; Wu, Ming-Tsang (Clinica chimica acta, 2014)
Studies have shown that melamine may be associated with urolithiasis. A more sensitive method is needed to analyze melamine in urinary stones to identify potential causes of urolithiasis. Here we compare the analytical methods of detecting melamine in urinary stones by Fourier transform infrared (FTIR) spectroscopy and matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) in the laboratory and clinic. First, we established the melamine detection limit in melamine-cyanurate standard by the methods of FTIR spectrophotometer and MALDI-TOF MS. Subsequently, we applied these two methods to 54 adult patients with upper urinary tract calcium urolithiasis. We found that the detection limit of melamine in melamine cyanurate standard by MALD-TOF MS was ~10,000-fold more sensitive than FTIR. We applied both instruments to 54 stone specimens from 54 calcium urolithiasis patients. In those without distinctive melamine pattern in the FTIR spectra, melamine could be detected by MALD-TOF MS in an additional 12 out of 42 subjects’ stone specimens (28.6%). Compared to MALD-TOF MS-negative subjects (n=30), those positive subjects (n=12) excreted significantly higher urinary melamine levels (P<0.05). Compared to FTIR, MALDI-TOF MS is a more sensitive method in detecting the content of melamine in melamine-containing kidney stones.